Exploring Dividend Policy Dynamics and Firm Valuation in the Technology Industry - Christo Wansley; Nathania Cordelia; Gabriela Veraria (IHSA Institute, 2024)
This research investigates the complex relationship between dividend policy and company value in the technology sector, characterized by rapid innovation, evolving market dynamics, and divergent investor preferences. Through a mixed-methods approach integrating quantitative analysis and qualitative insights, the study examines dividend policy variables and firm valuation metrics across a sample of technology firms. Empirical findings challenge conventional wisdom and theoretical expectations, revealing a modest or insignificant correlation between dividend yield and firm valuation metrics, and an unexpected negative correlation between payout ratio and firm valuation metrics. Exploring possible explanations for these unexpected findings highlights the influence of non-traditional value drivers, contextual factors, and industry dynamics on dividend policy practices. The research contributes to a deeper understanding of dividend policy dynamics in the technology sector, offering valuable insights for investors, managers, and policymakers navigating the complexities of capital allocation, growth investment, and shareholder value creation in a rapidly evolving and competitive market environment. Through continued research and dialogue, stakeholders can refine their understanding of dividend policy dynamics and inform strategic decision-making to foster sustainable growth and long-term prosperity in the technology industry and beyond.